2015
DOI: 10.1093/cid/civ1001
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Pregnancies Observed With Combined Use of the Levonorgestrel Contraceptive Implant and Efavirenz-based Antiretroviral Therapy: A Three-Arm Pharmacokinetic Evaluation Over 48 Weeks

Abstract: Women receiving efavirenz-based antiretroviral therapy plus a contraceptive implant had significantly lower levonorgestrel pharmacokinetics than women not receiving antiretroviral therapy. An unexpected high pregnancy rate (3/20, 15%) occurred in the efavirenz group, highlighting the clinical significance of this interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 15 publications
4
90
1
Order By: Relevance
“…[74][75][76] Interactions between efavirenz and Jadelle appear even more pronounced than with Implanon. [77,78] Women using an implant, who are also taking efavirenz, have higher pregnancy rates than those taking other antiretrovirals. The higher adherence to the implant, however, when compared with shortacting methods including injectable progestins, [79,80] means that despite this drug interaction, the implant remains highly effective in these women -more so than short-acting alternatives.…”
Section: Cmementioning
confidence: 99%
“…[74][75][76] Interactions between efavirenz and Jadelle appear even more pronounced than with Implanon. [77,78] Women using an implant, who are also taking efavirenz, have higher pregnancy rates than those taking other antiretrovirals. The higher adherence to the implant, however, when compared with shortacting methods including injectable progestins, [79,80] means that despite this drug interaction, the implant remains highly effective in these women -more so than short-acting alternatives.…”
Section: Cmementioning
confidence: 99%
“…Most of the pregnancies occurred on average 16 months after implants insertion suggesting a more rapid than expected decrease in levonorgestrel, which is expected to protect from pregnancy up to 5 years after insertion. In Uganda, one study showed that efavirenz reduces blood level of levonorgestrel and resulting to a higher contraceptive failure rate among women on both efavirenz based regimen and implants [3]. This strengthens the evidence that women on EFV-based regimens desiring contraception may need to be cautioned about a potential increased risk of pregnancy with use of HCI.…”
Section: Discussionmentioning
confidence: 79%
“…It is estimated that up to 14% of women living with HIV in SSA use implants [1]. However, there are controversial findings about potential interactions between hormonal contraceptive implants (HCI) and antiretroviral therapy (ART) [2][3][4]. In Swaziland, 12.4% of women taking efavirenz (EFV)-based regimens while onlevonorgestrel implant became pregnant, and EFV co-therapy were the only variable significantly correlated with pregnancy [1].…”
Section: Introductionmentioning
confidence: 99%
“…EO and LNG are primarily metabolized by the CYP pathway and are impacted by agents that induce or inhibit these metabolizing enzymes. Coadministration with agents known to induce this metabolic pathway may reduce plasma concentrations of these exogenous hormones, permitting escape ovulation and potentially resulting in contraceptive failure 9, 10. Since EO and LNG are not known inhibitors or inducers of CYP or glucuronyl transferase activity, it is unlikely that either would impact the PK of CAB.…”
Section: Introductionmentioning
confidence: 99%